PTFE mapping in gas diffusion media for PEMFCs using fluorescence microscopy - McCarthy,N; Chen,R; Offer,GJ; Thring,R (International Journal of Hydrogen Energy, 2016)
Differentiating between the various polytetrafluoroethylene based structures inside polymer electrolyte membrane fuel cells with a degree of certainty is necessary to optimize manufacturing processes and to investigate possible degradation mechanisms. We have developed a novel method using fluorescence microscopy for distinguishing the origin and location of PTFE and/or Nafion® in Membrane Electrode assemblies and the gas diffusion media from different sources and stages of processing. Fluorescent material was successfully diffused into the PTFE based structures in the GDM by addition to the ‘ink’ precursor for both the microporous layer and the catalyst layer; this made it possible to map separately both layers in a way that has not been reported before. It was found that hot pressing of membrane coated structures resulted in physical dispersion of those layers away from the membrane into the GDM itself. This fluorescence technique should be of interest to membrane electrode assembly manufacturers and fuel cell developers and could be used to track the degradation of different PTFE structures independently in the future.